Manajemen Event Indonesia Mods Mayday dalam Melestarikan Subkultur Mods di Kota Bandung - Juenva Adelia Bastari; Satya Indra Karsa (UNISBA Press, 2022)
Abstrac. In Indonesia, Mods are well known by many people, even many Mods groups are developing in Indonesia, one of which is in the city of Bandung. Mods are synonymous with scooters, clothes, and music, in the city of Bandung there is one group of Mods, namely Beatboys who regularly holds events that raise mods themselves. The event is called Indonesia Mods Mayday. Not only putting forward entertainment just like events in general, this event also has the aim of implementing a mods subculture in the city of Bandung, therefore to be able to realize it, proper planning is needed, good event management is also needed in order to achieve the desired results. This study aims (1) to find out the stages of research at theevent Indonesia mods mayday(2) to find out the design stages at theevent Indonesia mods mayday(3) to determine the stages of program planning at theeventtheevent. Indonesia mods mayday(4) to determine the stages of coordination atIndonesia mods mayday event Indonesia mods mayday. The theory used isManagement Theory Event Goldblatt's, the method used in this research is descriptive quantitative method, with data obtained from interviews with several sources, through documentation, observation and literature studies relevant to the research. Subjects in this study amounted to three people as the founder, executive vice event, members of the event Indonesia Mods Mayday. The results showed that the management of the event Indonesia Mods Mayday perform management event in five stages: research, design, planning, coordination, and evaluation. In the research phase of the event Indonesia Mods Mayday beginning to see the early history ofevent theand saw the desire and needs of the participants. In this case the committee event Indonesia Mods Mayday perform together Together to discussevent. this Design, this is done by choosing the theme of the event that is themed mods because it is from the beginning of the event Indonesia Mods Mayday greatly raised element mods, after the committee to think about perdanaan and location of the problem perdanaan event Indonesia Mods Mayday entirely from sponsors because at This event does not use a ticket system. Planning begins with some of the committee inspecting the location where thewill be held event. At this stage it must be arranged carefully and carefully considering this stage has a very important function. Planning is prepared based on the results of the data from the previous stages. Coordination, coordination carried out atin theeventthe Indonesia Mods Maydayform of communication in collaboration, and coordination was carried out to find out howdeveloping theevent was Indonesia Mods Mayday. Evaluation, carried out to each committee and evaluation of the participants present. Abstrak. Di Indonesia, Mods cukup dikenal oleh banyak orang , bahkan banyak kelompok Mods berkembang di Indonesia salah satunya di kota Bandung. Mods identik dengan skutter, pakaian, dan musik nya, di kota Bandung ada salah satu kelompok Mods yaitu Beatboys yang rutin mengadakan event yang mengangkat mods itu sendiri. Event itu bernamakan Indonesia Mods Mayday. Tidak hanya mengedepankan hiburan semata seperti event pada umumnya ,event ini juga memiliki tujuan untuk menerapkan subkultur mods di kota Bandung, oleh karena itu untuk bisa merealisasikannya diperlukan perencannan yang tepat, diperlukan juga pengelolaan manajemen event yang baik agar mencapai hasil yang diinginkan. Penelitian ini bertujuan (1) Untuk mengetahui tahapan riset pada event Indonesia mods mayday( 2)Untuk mengetahui tahapan desain pada event Indonesia mods mayday (3)Untuk mengetahui tahapan perencanaan program pada pada event Indonesia mods mayday( 4) Untuk mengetahui tahapan koordinasi pada pada event Indonesia mods mayday. Teori yang digunakan adalan Teori Manajemen Event Goldblatt, metode yang dugunakan dalam penelitian ini adalah metode deskriptif kuantitatif,dengan data yang diperoleh dari hasil wawancara terhadap beberapa narasumber, melalui dokumentasi, observasi dan studi pustaka yang relevan dengan penelitian. Subjek dalam penelitian ini berjumlah tiga orang selaku pendiri, wakil pelaksana acara, anggota event Indonesia Mods Mayday. Hasil penelitian menunjukan bahwa manajemen event Indonesia Mods Mayday melakukan manajemen event dalam lima tahap yaitu riset,desain,perencanaan,koordinasi, dan evaluasi. Pada tahap riset event Indonesia Mods Mayday awal mula dengan melihat sejarah awal event tersebut lalu meliha keinginan, dan kebutuhan para partisipan. Pada hal ini panitia event Indonesia Mods Mayday melakukan kumpul Bersama untuk membahas event ini. Desain, hal ini dilakukan dengan cara memilih tema event yaitu bertemakan mods karna memang dari awal event Indonesia Mods Mayday sangat mengangkat unsur mods, setelah itu panitia memikirkan masalah perdanaan dan lokasi untuk masalah perdanaan event Indonesia Mods Mayday sepenuhnya dari pihak sponsor karna pada event ini tidak menggunakan sistem tiket. Perencanaan , diawali dengan Sebagian panitia melakukan pemeriksaan lokasi yang akan menjadi tempat dilaksanakan event. Pada tahap ini harus di susun secara teliti dan matang mengingat tahap ini memiliki fungsi yang sangat penting. Perencanaan disusun berdasarkan hasil data dari tahapan sebelum nya. Koordinasi , koordinasi yang dilakukan pada event Indonesia Mods Mayday berupa komunikasi dalam berkerjasama, dan koordinasi dilakukan untuk mengetahui bagaimana perkembangan event Indonesia Mods Mayday. Evaluasi,dilakukan kepada masing- masing panitia dan evaluasi dari peserta yang hadir.